Should They Stay or Should They Go: Greek Housing on Campus as Substance Use Prevention?. Issue 3 (3rd July 2017) - Gibson, Sandy; Matto, Holly; Keul, Alyssa
Abstract : Greek life on college campuses offers many student benefits, including leadership skills and career networking, but is also associated with risk factors such as excessive alcohol use. This cross-sectional study compares hazardous alcohol and drug use, and use of protective behavioral strategies among non-Greek and Greek-affiliated students at 2 universities and differences among students at a university that offers on-campus Greek housing and a college with off-campus Greek housing. Findings reveal that Greek-affiliated students report more alcohol use, and no difference in drug use or in protective behavioral strategies, than non-Greek students. Among Greek students, those living in on-campus Greek housing report significantly lower alcohol use than students residing in off-campus Greek housing. Regardless of Greek status, students at the college with off-campus Greek housing are significantly more likely to use alcohol and marijuana in a fraternity or sorority house than students at the university with on-campus Greek housing.